A critical role of PvFtsH2 in the degradation of photodamaged D1 protein in common bean. (1st June 2021) - Xu, Kun; Zhu, Jinlong; Zhai, Hong; Wu, Hongyan; Gao, Yi; Li, Yuzhuo; Zhu, Xiaobin; Xia, Zhengjun
Abstract: Light is required for initiating chloroplast biogenesis and photosynthesis; however, the photosystem II reaction center (PSII RC) can be photodamaged. In this study, we characterized pvsl1, a seedling-lethal mutant of Phaseolus vulgaris . This mutant showed lethality when exposed to sunlight irradiation and a yellow-green leaf phenotype when grown in a growth chamber under low-light conditions. We developed 124 insertion/deletion (INDEL) markers based on resequencing data of Dalong1 and PI60234, two local Chinese common bean cultivars, for genetic mapping. We identified Phvul.002G190900, which encodes the PvFtsH2 protein, as the candidate gene for this pvsl1 mutation through fine-mapping and functional analysis. A single-base deletion occurred in the coding region of Phvul.002G190900 in the pvsl1 mutant, resulting in a frameshift mutation and a truncated protein lacking the Zn 2+ metalloprotease domain. Suppressed expression of Phvul.002G190900 at the transcriptional level was detected, while no change in the subcellular localization signal was observed. The seedlings of pvsl1 exhibited hypersensitivity to photoinhibition stress. In the pvsl1 mutant, abnormal accumulation of the D1 protein indicated a failure to rapidly degrade damaged D1 protein in the PSII RC. The results of this study demonstrated that PvFtsH2 is critically required for survival and maintaining photosynthetic activity by degrading photodamaged PSII RC D1 protein in common bean.